Technology gaps and leaps in the sustainable development of English cereal and general cropping farms - Iliakis, Konstantinos; Gadanakis, Yiorgos; Park, Julian (My University, 2017)
Identifying and assessing technology gaps and technology leaps observed in the agricultural productivity change analysis is of paramount importance since it enables the identification of a set of effects that influence the way that inputs are transformed into outputs and resources are allocated between diversified farm activities. Previous studies have ignored the importance of heterogeneity between different farming systems and their characteristics and have also failed to account for the different rates of technology absorption with respect to an unrestricted universal production frontier considering simultaneous generation of main products and by-products. Furthermore, the technology leaps defined as varying rates of technology absorption over time with respect to the unrestricted universal production frontier may lead to miss-specified local production functions and biased efficiency and productivity change estimates. The analysis focused on the regional variation of the production environment, farm specialisation and level of engagement as constraints to productivity gains. By considering two different levels of endogenous and exogenous heterogeneity in the production environment, the analysis used data from the Farm Business Survey of English arable farms for the years 2005-2013 and employed the parametric stochastic meta-frontier analysis to measure sustainable productivity change as producers engage into agricultural and diversified activities as alternative sources of income. The model approaches simultaneous value-adding generation processes to reveal the relationship between change in producers’ endowments and productivity gains in a network application under uncertainty.
Keywords: technology gaps; technology leaps; meta-frontier analysis; productivity change